Occupational exposures to blood and body fluids among healthcare workers in Ethiopia: a systematic review and meta-analysis - Biniyam Sahiledengle; Yohannes Tekalegn; Demelash Woldeyohannes; Bruce John Edward Quisido (Environmental Health and Preventive Medicine, 2020)
Abstract Background Occupational exposure to blood and body fluids is a major risk factor for the transmission of blood-borne infections to healthcare workers. There are several primary studies in Ethiopia yet they might not be at the national level to quantify the extent of occupational blood and body fluid exposures (splash of blood or other body fluids into the eyes, nose, or mouth) or blood contact with non-intact skin among the healthcare workers. This systematic review and meta-analysis aimed to estimate the pooled prevalence of occupational blood and body fluid exposure of healthcare workers in Ethiopia. Methods PubMed, Science Direct, Hinari, Google Scholar, and the Cochrane library were systematically searched; withal, the references of appended articles were also checked for further possible sources. The Cochrane Q test statistics and I 2 tests were used to assess the heterogeneity of the included studies. A random-effects meta-analysis model was used to estimate the lifetime and 12-month prevalence of occupational exposure to blood and body fluids among healthcare workers in Ethiopia. Results Of the 641 articles identified through the database search, 36 studies were included in the final analysis. The estimated pooled lifetime and 12-month prevalence on occupational exposure to blood and body fluids among healthcare workers were found to be at 54.95% (95% confidence interval (CI), 48.25–61.65) and 44.24% (95% CI, 36.98-51.51), respectively. The study identified a variation in healthcare workers who were exposed to blood and body fluids across Ethiopian regions. Conclusion The finding of the present study revealed that there was a high level of annual and lifetime exposures to blood and body fluids among healthcare workers in Ethiopia.